1997
DOI: 10.1021/la9604285
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric Effects on the Structure of Micelles of Alkyl Maltosides in Water

Abstract: Structures formed by self-assembly of α- and β-1-n-dodecyl d-maltosides in water depend on the configuration at the anomeric center. The α-anomer forms quasi-spherical aggregates, while the β-maltoside forms larger oblate ellipsoidal micelles. This difference in behavior suggests that the configuration of the head group influences the orientation of the polar residue and hence the packing of monomers during self-assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
140
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(177 citation statements)
references
References 9 publications
36
140
0
Order By: Relevance
“…These results suggest that high DM concentrations can affect the Rho oligomeric structure and slow down the Gt activation process. Our results are in agreement with a previous study where a decrease in Gt activity with increasing DM concentration was reported (47,48). This experiment is not reliable for the cross-linked Rho, since modification of the surface of the receptor alters activation of Gt (57)(58)(59).…”
Section: Oligomeric Structure Of Rho In Chaps-we Also Investigated Thsupporting
confidence: 90%
See 2 more Smart Citations
“…These results suggest that high DM concentrations can affect the Rho oligomeric structure and slow down the Gt activation process. Our results are in agreement with a previous study where a decrease in Gt activity with increasing DM concentration was reported (47,48). This experiment is not reliable for the cross-linked Rho, since modification of the surface of the receptor alters activation of Gt (57)(58)(59).…”
Section: Oligomeric Structure Of Rho In Chaps-we Also Investigated Thsupporting
confidence: 90%
“…The molecular mass of the Rho monomer and dimer estimated by SDS-PAGE is ϳ36 and 72 kDa, respectively. 3 The aggregation number of DM is 132 (48), and the molecular mass of DM micelles is ϳ67,399 Da (48). The sizes of the Rho monomer and Rho dimer complexes with DM seen in the size exclusion chromatography experiments (ϳ90 -100 and ϳ140 -160 kDa, respectively) agree with the sums of the protein and micellar molecular masses (103,500 Da (monomer) and 149,500 Da (dimer)).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…We use their values for C 10 G 2 and C 12 G 2 (ESI, † Table 5) together with an interpolated value for C 11 G 2 . The values are in good agreement with data from independent sources 47,48 (see also ref. 8).…”
Section: Determination Of Cmcsupporting
confidence: 89%
“…5a). In fact, a study by Dupuy et al (1997) indicates that -maltoside molecules form oblate ellipsoidal micelles in water. Nevertheless, an attempt to simulate the detergent-solubilized truncated KcsA K + channel was able to essentially reproduce the low-angle scattering features including the characteristic minimum near q = 0.11 Å À1 , where q ¼ ð4=Þ sin , 2 is the scattering angle and is the wavelength (Fig.…”
Section: Figurementioning
confidence: 99%